Atividade e participação de crianças e adolescentes com paralisia cerebral atendidos pelo serviço de fisioterapia pediátrica de uma universidade no interior do Amazonas - Costa, Renata Maila da Silva (Brasil, 2025)
Objective: To characterize the activities and participation of children and adolescents with cerebral palsy at a physiotherapy outpatient clinic at a university in the interior of Amazonas. Method: Descriptive, retrospective, cross-sectional study based on medical records. Children and adolescents aged zero to 18 years old, evaluated by the pediatric physiotherapy sector of the Institute of Health and Biotechnology - ISB in 2022 and the first half of 2023, were included. Patients with missing data, outside the established period, and medical records of the same patient from periods after the first evaluation were excluded. 17 patients constituted the final sample. Data were submitted to descriptive analysis using Jamovi software, version 1.6.23.0. Results: Most participants were male (64,7%), with an age range of 1 to 4 years (52.9%) and a predominant family income between 1 and 2 minimum wages for 8 (47,1%). Regarding diagnosis, 8 (47,1%) had bilateral spastic cerebral palsy, with quadriplegia being the most common type for 7 (41,2%). In activities, 8 (47,1%) were level V in the Gross Motor Function Classification System (GMFCS) and 5 (29,4%) levels I and IV in the Manual Ability Classification System (MACS). In participation, 11 (64,7%) were not involved in school activities and 7 (41,2%) had little involvement in playing with friends. Conclusion: In this study, children and adolescents with CP presented significant limitations in their activities involving gross motor function and self-care, and restricted school participation. There is a need to deepen the understanding of the functionality and disability of these individuals who live far from large urban centers, especially those who reside in remote areas of the country, with the aim of aligning health and social assistance service policies and actions for this population.